Exploring the Intrinsic Motivation of Experienced MMORPG Players: Case “The Elder Scrolls Online” - Taipalharju, Jussi (My University, 2025)
As video games have become an extremely popular form of entertainment, the business opportunities in the field are ever increasing. While motivation in video games has been extensively studied, reasons to continue playing a game in the long-term have not been thoroughly researched. Addressing this research gap is important not only for the academic value, but also for game developers who increasingly adopt methods of continuous development and subscription-based business models that rely on long-term player commitment. This thesis focuses on how experienced players are intrinsically motivated to continue playing The Elder Scrolls Online and how engaging in different in-game activities is reflected in the intrinsic motivation. The data from semi-structured interviews are connected to the Self-Determination Theory framework in an abductive analysis conforming to the Gioia method. The data contain a plethora of detailed player experiences that would be difficult to capture in quantitative studies. Key findings include a suggested interaction between the basic psychological needs for autonomy, competence and relatedness and a pattern in the order of satisfaction of the needs suggested by the participants’ experiences. Implications for both academic research and practical game development are discussed.
Keywords: MMORPG, video games, intrinsic motivation, Self-Determination Theory